Emotional Clarity and Stress Vulnerability as Predictors of Cognitive Failures - Yang, Jiantang; Herawati, Netty; Namjoo, Farhad (Journal of Personality and Psychosomatic Research (JPPR), 2024)
To investigate the relationships between emotional clarity, vulnerability to stress, and cognitive failures, and to determine the predictive value of emotional clarity and vulnerability to stress on cognitive failures. This cross-sectional study included 330 participants selected based on the Morgan and Krejcie table. Data were collected using the Cognitive Failures Questionnaire (CFQ), the Trait Meta-Mood Scale (TMMS) for emotional clarity, and the Perceived Stress Scale (PSS). Pearson correlation and linear regression analyses were conducted using SPSS version 27. Descriptive statistics indicated mean scores of 35.24 (SD = 9.87) for cognitive failures, 26.78 (SD = 7.65) for emotional clarity, and 29.43 (SD = 8.31) for vulnerability to stress. Pearson correlation analysis showed significant relationships between cognitive failures and emotional clarity (r = -0.45, p < 0.001) and vulnerability to stress (r = 0.53, p < 0.001). Regression analysis revealed that both emotional clarity (B = -0.48, SE = 0.09, β = -0.32, t = -5.31, p < 0.001) and vulnerability to stress (B = 0.67, SE = 0.08, β = 0.45, t = 8.37, p < 0.001) were significant predictors of cognitive failures, accounting for 38% of the variance (R² = 0.38, F(2, 327) = 99.65, p < 0.001). The study found that higher emotional clarity is associated with fewer cognitive failures, while higher vulnerability to stress is linked to increased cognitive failures. Both emotional clarity and vulnerability to stress significantly predict cognitive failures, highlighting their importance in cognitive performance. These findings suggest that interventions aimed at enhancing emotional clarity and managing stress could reduce cognitive failures.